F‐domain valency determines outcome of signaling through the angiopoietin pathway. (26th October 2021) - Zhao, Yan Ting; Fallas, Jorge A; Saini, Shally; Ueda, George; Somasundaram, Logeshwaran; Zhou, Ziben; Xavier Raj, Infencia; Xu, Chunfu; Carter, Lauren; Wrenn, Samuel; Mathieu, Julie; Sellers, Drew L; et al.
Abstract: Angiopoietins 1 and 2 (Ang1 and Ang2) regulate angiogenesis through their similar F‐domains by activating Tie2 receptors on endothelial cells. Despite the similarity in the underlying receptor‐binding interaction, the two angiopoietins have opposite effects: Ang1 induces phosphorylation of AKT, strengthens cell–cell junctions, and enhances endothelial cell survival while Ang2 can antagonize these effects, depending on cellular context. To investigate the molecular basis for the opposing effects, we examined the phenotypes of a series of computationally designed protein scaffolds presenting the Ang1 F‐domain in a wide range of valencies and geometries. We find two broad phenotypic classes distinguished by the number of presented F‐domains: Scaffolds presenting 3 or 4 F‐domains have Ang2‐like activity, upregulating pFAK and pERK but not pAKT, while scaffolds presenting 6, 8, 12, 30, or 60 F‐domains have Ang1‐like activity, upregulating pAKT and inducing migration and vascular stability. The scaffolds with 6 or more F‐domains display super‐agonist activity, producing stronger phenotypes at lower concentrations than Ang1. Tie2 super‐agonist nanoparticles reduced blood extravasation and improved blood–brain barrier integrity four days after a controlled cortical impact injury. Synopsis: An array of synthetic ligands designed computationally allows to precisely delineate the molecular basis of the Angiopoietin‐Tie2 pathway and the role of receptor oligomerization and transmembrane signaling. F‐domain valency determines the activation of pAKT, pERK, and pFAK downstream of Tie2. High valency F‐domain superagonists promote integrin colocalization and actin rearrangement. F‐domain scaffold superagonists promote vascular stabilization in vitro and in vivo . Abstract : An array of synthetic ligands designed computationally allows to precisely delineate the molecular basis of the Angiopoietin‐Tie2 pathway and the role of receptor oligomerization and transmembrane signaling.